HUBUNGAN FAKTOR USIA, PENGETAHUAN DAN EKONOMI TERHADAP KEJADIAN (KEK) PADA IBU HAMIL DI PUSKESMAS BARA-BARAYA TAHUN 2024 - Munawwarah. M, St.; Rahmat, Basuki; Irwan, Hadrian; Sari, Wahyuni Kartika (JURNAL KESEHATAN DELIMA PELAMONIA, 2024)
Background : Due to their higher nutritional needs, pregnant women are among the most vulnerable groups in society. The World Health Organization (WHO) estimates that 35–75% of pregnant women worldwide suffer from chronic energy deficiency (CED), which is one of the most common nutritional problems. Chronic Energy Deficiency is a condition in which the body does not receive adequate nutrients due to an imbalance in energy and protein intake, ultimately affecting fetal development. Objective: To determine the relationship between the prevalence of chronic energy deficiency among pregnant women at the Bara-Baraya Community Health Center (Puskesmas Bara-Baraya) in 2024. Methods: This study used age, knowledge, and economic status as independent variables, while the occurrence of chronic energy deficiency among the study subjects, observed and measured simultaneously, was the dependent variable. An analytical statistical test was used to explain the research findings, with a total sample of 32 pregnant women examined at the Bara-Baraya Community Health Center in Makassar City between March and April 2024. The sampling method used was accidental sampling. Results and Conclusion: The study showed that: There is a significant relationship between maternal age and the incidence of chronic energy deficiency among pregnant women at the Bara-Baraya Health Center in 2024 (significance value = 0.01). There is a significant relationship between maternal knowledge and the incidence of chronic energy deficiency (significance value = 0.02). There is also a significant relationship between economic status and the incidence of chronic energy deficiency (significance value = 0.04). Thus, the prevalence of CED among pregnant women at the Bara-Baraya Community Health Center in 2024 is associated with age, knowledge, and economic factors.